The determinants of corporate risk management practices and the impact of hedging activities on firms’ risk: evidences from German nonfinancial companies - Leva, Noemi (2016)
Corporate risk management through derivative hedging activity has been growing in importance in recent years, following the ever increasing volume of financial products traded and the implications of the financial crisis. Extensive research has been conducted on hedging strategies mainly considering the rationale for corporate hedging. Nevertheless, few studies have inspected the effects on firm risk and still mixed results are reported in literature. In this research project, an analysis on the driving factors for corporate risk management practices has been conducted. The final sample comprises 397 German nonfinancial companies observed over a period of 6 years, from 2010 to 2015. Data on hedging activities was manually collected from firms’ annual reports. The empirical investigation has been performed through the use of a combined approach of univariate and multivariate logistic regressions. Findings suggest that foreign exchange rate exposure, size and tax loss carry forward are significant determinants of firms’ derivative hedging activity. Tests have been iterated on unbiased non-hedgers and non FX-hedgers samples. The results evidence that a more inclusive definition of hedging is necessary in order to fully detect the links between hedging and expected costs of financial distress. Finally, ordinary least square regressions have shown evidences that hedging reduces firms’ risk of German nonfinancial companies which thus use derivatives for hedging rather than for speculative motives.